2018
DOI: 10.2118/180307-pa
|View full text |Cite
|
Sign up to set email alerts
|

Transient Coupling of Swab/Surge Pressure and In-Situ Stress for Wellbore-Stability Evaluation During Tripping

Abstract: Summary This paper identifies wellbore-stability concerns caused by transient swab/surge pressures during deepwater-drilling tripping and reaming operations. Wellbore-stability analysis that couples transient swab/surge wellbore-pressure oscillations and in-situ-stress field oscillations in the near-wellbore (NWB) zone in deepwater drilling is presented. A transient swab/surge model is developed by considering drillstring components, wellbore structure, formation elasticity, pipe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…Finally, after integrating swab and surge pressure, a drilling mud that was initially in the safe region can slip out into the unstable region, therefore the time dependent safe mud weight should be employed to provide accurate results for the wellbore stability analysis. These findings are in line with the findings of (Zhang et al 2018) who showed that incorporating swab/surge pressure into the wellbore stability study resulted in a smaller mud weight window than expected.…”
Section: Stress Regimessupporting
confidence: 91%
See 3 more Smart Citations
“…Finally, after integrating swab and surge pressure, a drilling mud that was initially in the safe region can slip out into the unstable region, therefore the time dependent safe mud weight should be employed to provide accurate results for the wellbore stability analysis. These findings are in line with the findings of (Zhang et al 2018) who showed that incorporating swab/surge pressure into the wellbore stability study resulted in a smaller mud weight window than expected.…”
Section: Stress Regimessupporting
confidence: 91%
“…The low permeability of the rock formation utilized in this study (5md) also prevents the variation of the pore pressure with the swab and surge pressure in the near wellbore region. The influence of transient swab and surge pressure on the real-time wellbore stability was also examined by (Zhang et al 2018) and they got opposite results with the current study: Their results showed that transient swab and surge pressure affect pore fluid pressure in the surrounding wellbore area, and the effect on the pore pressure declines when going farther away from the wellbore. The discrepancy between the two results is due to the fact that the rock permeability utilized in this simulation (5md) is lower than the permeability employed in the (Zhang et al 2018) study (10 md).…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…Zamanipour et al [8] investigated the wellbore stress distribution and wellbore stability when transient surge stress is generated in a directional wellbore during tripping process. Zhang et al [9] conducted wellbore stability analysis by coupling transient swab/surge model and poromechanical solution during tripping and reaming processes and proposed a work flow to obtain safe mud-weight window. Meng et al [10] developed a coupled poroelastodynamic model to obtain dynamic stress distribution around the wellbore.…”
Section: Introductionmentioning
confidence: 99%